A Note on Indirect Tax Evasion - Arias, Roberto José (2005)
This paper checks out the sensibility of indirect tax evasion models to assumptions about: i) tax function, ii) audit probability function, iii) risk aversion and iv) how tax evasion decisions occur. We found out that under perfect competition: i) the optimum level of tax evasion for ad valorem and specific taxes are equal but static comparative are not, ii) ad valorem tax evasion is lowest if the audit probability is decreasing with respect to the firm output, iii) risk aversion models produce similar results than direct cost of evasion models, but results are more conclusive when the risk is additive.